Perfluoroalkyl substances in water, sediment, and fish from a subtropical river of China: Environmental behaviors and potential risk. (February 2022) - Wang, Siquan; Cai, Yizhi; Ma, Liya; Lin, Xiaoping; Li, Qin; Li, Yongyu; Wang, Xinhong
Abstract: Perfluoroalkyl substances (PFAS) in water, sediment and fish were analyzed from a subtropical river, Jiulong River in the southeast of China, to character the sources, seasonal variations, bioconcentration and potential risk. PFAS in water, sediment, muscle and liver tissues of fish ranged from 2.5 to 410 ng L −1, 0.24–1.9 ng g −1 dw, 25–100 and 35–1100 ng g −1 ww, respectively. Generally, perfluorohexanoic acid (PFHxA) was the dominant compound in water, while, perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS) were the dominant compounds in sediment and fish tissues. High concentrations of PFAS in water were found near the machinery manufacturing and paper packaging plants in the north branch of Jiulong River. PFAS during the dry season were significantly ( P < 0.01) higher than that during the normal season and wet season. The Kd of PFAS increased with the carbon chain length, and perfluoroalkyl sulfonic acids (PFSAs) exhibited higher Kd values than perfluoroalkyl carboxylic acids (PFCAs), indicating these long chain PFAS tended to be adsorbed by sediment. Long chain PFAS exhibited high bioconcentration factors (BCFs), while short and medium carbon chain PFAS had weak bioconcentration capacity. The hazard ratios (HR) suggested that frequent consumption of river fish may pose health risks to local population. Graphical abstract: Image 1 Highlights: PFAS exhibited different composition profiles in water, sediment and fish. Industrial activities contributed PFAS to the Jiulong River. Carbon chain length and functional groups affected Kd values. PFAS tended to accumulate in the liver of fish.